Penerapan Hukum Terhadap Penyebar Video Porno Implementasi Undang-Undang Nomor 44 Tahun 2008 Tentang Pornografi - Gusti Heliana Safitri; Hendy Indra Pratama (Scholar Center, 2021)
This study aims to determine the qualifications of the crime of distributing pornographic videos in the view of criminal law and to determine the application of material criminal law to the crime of spreading pornographic videos. This research method uses a normative juridical approach, secondary data from library research techniques. Then it was analyzed qualitatively and then presented descriptively. The results of the research conducted by the author that the act of pornography is a crime that is private in nature so that law enforcement against pornography eradication there are many difficulties. One of the inhibiting factors for eradicating pornography is the lack of cooperation from the community and various parties in reporting this crime. The application of criminal law has a tendency to be influenced by the structure of society, which is an obstacle that allows the application of criminal law to be carried out and can provide obstacles that lead to the application of criminal law cannot be carried out or cannot be maximized. The elements of a pornographic crime consist of a subjective element, namely an error, which means that the act was intentionally or with its consent, and an objective element, namely an act (to be) which means an object or model that contains pornographic content. (2) The crime of pornography is carried out based on the Criminal Procedure Code unless otherwise stipulated in Law Number 44 of 2008.